The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/tnsci-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone attenuates brain injury via an antioxidative pathway in a status epilepticus rat model

Abstract: Status epilepticus (SE) is a common, lifethreatening neurologic disorder characterized by acute, prolonged epileptic seizures. The incidence rate of SE is about 0.05 to 0.1% in the general population and 1.1 to 14% in the epileptic population. SE has a poor prognosis because seizures that cannot be terminated quickly result in irreversible brain injury. It is known that multiple factors are involved in the pathogenesis of brain injury induced by SE, one of which is oxidative stress [1][2]. The generation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…TQ crosses the blood brain barrier and exerts neuromodulatory activities. It has a neuroprotective effect and improves brain injuries resulting from Parkinson's disease [5] and status epilepticus [6]. It is also useful in the treatment of glial tumours by inducing apoptosis of glial tumour cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…TQ crosses the blood brain barrier and exerts neuromodulatory activities. It has a neuroprotective effect and improves brain injuries resulting from Parkinson's disease [5] and status epilepticus [6]. It is also useful in the treatment of glial tumours by inducing apoptosis of glial tumour cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scientific findings show that TQ exerts a protective effect against pilocarpine-induced brain injury and it ameliorates brain damage through an antioxidant pathway in a status epilepticus rat model 31 . It has also been shown that TQ reduces lipid peroxidation in the hippocampal tissue of rats in a global cerebral ischemia-reperfusion injury model…”
mentioning
confidence: 99%
“…[12] Nigella sativa oil (NSO) being a natural antioxidant essential oil, [12,13] with proven neuro-protective efficacies, [12,13,15,18.38] was explored as a potent neuroprotective substance against DDVP neurotoxicity. And effectively, NSO intervention in this study was vital in preventing the out-burst of both ROS and NO productions in the hippocampus of the DDVP and/ or NSO exposed rats, an effect that could be supported by its previously reported antioxidant efficacy against models of neurotoxicity [12,13,19,[39][40][41] The antioxidant effects of NSO against DDVP we observed in this study as well as those reported in other neurotoxic models, [12,13] further strengthen the efficacy of NSO against OPinduced neurological deficits. [42,43] Co-administration of NSO with DDVP also revealed that NSO was able to preserve the cholinergic integrity of the hippocampus, by minimizing AChE deactivation induced by DDVP in the exposed rats.…”
Section: Discussionmentioning
confidence: 65%
“…All of the above effects of the Nigella sativa oil can be associated with its antioxidant capacities which prevent oxidative damages, a process implicated in the initiation of pathological processes in various neurological diseases. [19,[39][40][41][42] Therefore we conclude that interventional administration of NSO in this study had hippocampal neuroprotective functions against the effects of DDVP exposure, and that this predominantly occurred through the modulation of oxidative and neurogenic functions.…”
Section: Resultsmentioning
confidence: 88%